2017
DOI: 10.1002/eat.22723
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cognitive behavioral therapy for eating disorders adapted for a group setting

Abstract: This study demonstrated that a group version of CBT-E can be effective at reducing eating disorder psychopathology in a transdiagnostic sample of individuals with eating disorders. Group CBT-E could provide a means of increasing availability of evidence-based treatment for eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 47 publications
(62 reference statements)
4
63
1
1
Order By: Relevance
“…In one study (Allen et al, ) that recruited patients with AN, BN, or EDNOS, subgroup analyses revealed that attrition was significantly higher in those with the former diagnosis. However, Wade et al () found no difference in attrition between patients with AN, BN, BED, or OSFED.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study (Allen et al, ) that recruited patients with AN, BN, or EDNOS, subgroup analyses revealed that attrition was significantly higher in those with the former diagnosis. However, Wade et al () found no difference in attrition between patients with AN, BN, BED, or OSFED.…”
Section: Resultsmentioning
confidence: 99%
“…All randomized trials were conducted in an outpatient treatment setting, and all but one (Thompson‐Brenner et al, ) reported findings using intent‐to‐treat (ITT) analyses. Three trials recruited women only (Thompson‐Brenner et al, ; Wade et al, ; Zipfel et al, ) and one trial did not report on the sex composition of their sample (Allen et al, ). For the remainder of studies, the majority of participants were women (i.e., >90%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, the recent paper by Le, Hay, Wade, Touyz, and Mihalopoulos (in press) addresses just this point, showing CBT‐ED to be a cost‐effective treatment for many of our patients. It is also possible to get good results with CBT‐ED delivered in a group format (Jones & Clausen, ; Wade, Byrne, & Allen, ). Finally, and again with low‐cost interventions in mind, Chithambo and Huey () show the potential of CBT‐ED as a prevention tool, giving results that are comparable with those of dissonance‐based interventions.…”
Section: The Content Of This Virtual Issuementioning
confidence: 99%